Rapid isolation of monosialogangliosides from bovine brain gangliosides by selective-overload chromatography. - O Koul; M Prada-Maluf; RH McCluer; MD Ullman (Journal of Lipid Research, 1991)
A procedure for rapid isolation of monosialogangliosides from purified bovine brain gangliosides has been developed. It utilizes the selective difference in association between monosialogangliosides and polysialogangliosides for the ion-exchange resin Q-Sepharose. When the ion-exchange column is overloaded with a bovine brain ganglioside mixture in the proper ganglioside to column bed-volume ratio, the polysialogangliosides are selectively retained by the column while the monosialogangliosides emerge with the void volume without the use of salt for elution. With the critical ganglioside to bed-volume ratio (1 g:8.32 ml), and an appropriate column bed-height to column radius ratio of 6.9, monosialogangliosides are reproducibly obtained in high purity with greater than 90% yield. The method has been used at both the analytical and preparative scale. We call this separation technique selective-overload chromatography.